Disease-free survival and the prognostic factors affecting disease-free survival in patients with medullary thyroid carcinoma: a multicenter cohort study - Zuhur, Sayid Shafi; Ozturk, Beyza Olcay; Keskin, Umran; Uysal, Serhat; Hacioglu, Aysa; Avci, Ugur; Elbuken, Gulsah (Springer, 2024)
Purpose Despite several factors that may have been associated with poor disease-free survival (DFS) in patients with medullary thyroid carcinoma (MTC), only a few studies have evaluated the prognostic factors affecting DFS in MTC patients. Therefore, this study evaluated the prognostic factors affecting DFS, in a large number of patients with MTC. Methods Patients treated for MTC were retrospectively analyzed. Patients were stratified as having persistent/recurrent disease and no evidence of disease (NOD) at the last follow-up. The factors affecting DFS after the initial therapy and during the follow-up period were investigated. Results This study comprised 257 patients [females 160 (62.3%), hereditary disease 48 (18.7%), with a mean follow-up time of 66.8 +/- 48.5 months]. Persistent/recurrent disease and NOD were observed in 131 (51%) and 126 (49%) patients, respectively. In multivariate analysis, age > 55 (HR: 1.65, p = 0.033), distant metastasis (HR: 2.41, p = 0.035), CTN doubling time (HR: 2.7, p = 0.031), and stage III vs. stage II disease (HR 3.02, p = 0.048) were independent predictors of persistent/recurrent disease. Although 9 (8%) patients with an excellent response after the initial therapy experienced a structural recurrence, the absence of an excellent response was the strongest predictor of persistent/recurrent disease (HR: 5.74, p < 0.001). Conclusions The absence of an excellent response after initial therapy is the strongest predictor of a worse DFS. However, a significant proportion of patients who achieve an excellent response could experience a structural recurrence. Therefore, careful follow-up of patients, including those achieving an excellent response is essential.
Keywords: Medullary thyroid carcinoma; Disease-free survival; Excellent response; Prognosis